PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KANCING GEMERINCING DISERTAI LKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPS SMAN 14 PADANG - Syafira, Noni; Husna, Husna; Haryono, Yulia (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research is motivated by the lack of results of learning mathematics class XI IPS Padang SMAN 14 school year 2013/2014. This problem can be seen from the study of mathematics is still focused on teacher, students just listen and record the subject matter without understanding the material, students are less motivated to learn mathematics, comprehension of the concept of mathematical ability of students is still low, and equitable distribution of responsibility in the discussion is still less. This study aims to determine whether students comprehension of mathematical concepts by implementing cooperative learning techniques âKancing Gemerincingâ with Student Worksheet (LKS) is better than the students comprehension of concepts with conventional learning in social studies class XI student of SMAN 14 Padang. This research is a research experiment. The population in this study were all students of class XI social SMAN 14 Padang and who is enrolled in the school year 2013/2014. The sampling technique is random sampling, XI IPS 3 selected as the experimental class and Â XI IPS 4 as the control class. The instrument used Â in this research is the final test study with reliability 0.92. Based on the analysis of data, average student learning outcomes experimental class is 74.88 with standard deviation 11.14 and the average value of the control class is 54.83 with a standard deviation Â 22.64. Because the two classes are normally distributed sample is not homogeneous but the data was analyzed by statistical test Â where Â = 3.9081 so that the research hypothesis is accepted. Thus, it can be concluded that the students comprehension of mathematical concepts by implementing cooperative learning techniques âKancing Gemerincingâ with Student Worksheet (LKS) better comprehension of the concept of the conventional learning on students a class XI IPS student of SMA Negeri 14 Padang at the level of 95%.